The determination of polymeric derivatives of guanidine in disinfectants by two-phase titration - O. I. Kozoor; L. A. Nosikova; K. A. Shestakov; A. N. Kochetov (Тонкие химические технологии)
The article considers the results of identifying the disinfectant water-soluble guanidines polymers by means of methods including spectrophotometry, infrared spectroscopy, fluorescence analysis, as well as the use of gold nanoparticles. The present work describes the results of polyhexamethyleneguanidine (PHMG) identification in finished compositions. It is shown that auxiliary components such as quaternary ammonium compounds prevent the identification of the PHMG in the mixture. So, most known methods are ineffective or require additional manipulations. The method of quantitative analysis of polyhexamethyleneguanidine (PHMG) and polyhexamethylenebiguanidine (PHMB) in disinfectants by means of two-phase titration with sodium dodecyl sulfate in the presence of bromophenol blue indicator was proposed. The end point was detected visually. This method allows taking into account the additive contributions of quaternary ammonium compounds in PHMG titration results. In this case, the titration at all stages of the determination of PHMG is conducted with sodium dodecy sulfate solutions with the same concentrations and the same weighed portions of sample are taking. Other disinfectants, namely hydrogen peroxide, alcohols, primary, secondary, tertiary amines, including N,N-bis(3-aminopropyl)dodecylamine present in the solution do not interfere with the identification of PHMG.